2023
DOI: 10.1002/adom.202300323
|View full text |Cite
|
Sign up to set email alerts
|

Realizing Color‐Tunable and Time‐Dependent Ultralong Afterglow Emission in Antimony‐Doped CsCdCl3 Metal Halide for Advanced Anti‐Counterfeiting and Information Encryption

Abstract: Long afterglow luminescent materials have captured intense attention for their unique applications in biological imaging, photodynamic therapy, and optical anti-counterfeiting. However, achieving highly efficient and tunable ultralong afterglow emission in all-inorganic metal halides is an open challenge. Herein, Sb 3+ -doped hexagonal CsCdCl 3 metal halide is reported via hydrothermal reaction. Upon photoabsorption, the as-synthesized compounds exhibit dual-emission bands with a photoluminescence quantum yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…In Figure S16, the excitation spectrum of KCdCl 3 :Sb 3+ monitored at 554 nm exhibits three bands in the 250−400 nm region, similar to that of CsCdCl 3 :Sb 3+ in previous work. 14 Under excitation at 285, 340, and 327 nm, the emission spectra of KCdCl 3 :Sb 3+ indicate a similar profile with a broad emission covering 400−700 nm. The results demonstrate that there is only one PL center in the KCdCl 3 :Sb 3+ .…”
Section: Analysis Of Thermodynamicmentioning
confidence: 85%
See 3 more Smart Citations
“…In Figure S16, the excitation spectrum of KCdCl 3 :Sb 3+ monitored at 554 nm exhibits three bands in the 250−400 nm region, similar to that of CsCdCl 3 :Sb 3+ in previous work. 14 Under excitation at 285, 340, and 327 nm, the emission spectra of KCdCl 3 :Sb 3+ indicate a similar profile with a broad emission covering 400−700 nm. The results demonstrate that there is only one PL center in the KCdCl 3 :Sb 3+ .…”
Section: Analysis Of Thermodynamicmentioning
confidence: 85%
“…Many derivatives of Cd-based AIHPs have been developed host lattices for various luminescent materials through the substituting the Cd 2+ with different dopants, such as Sb 3+ , Sn 2+ , and Mn 2+ (Table S1). , The Sb 3+ and Mn 2+ -codoped 2D AIHPs Cs 3 Cd 2 Cl 7 :Sb 3+ ,Mn 2+ have ultralong afterglow emission at 579 nm. The Sb 3+ /Mn 2+ doped the hexagonal CsCdCl 3 AIHPs lead to red/orange afterglow emission with the longest duration after removal of the UV excitation, which is expected for application in biological imaging, photodynamic therapy, and optical anticounterfeiting. ,, The Cs 2 CdCl 4 :Sb 3+ nanoplatelets exhibit cyan emission with photoluminescence quantum yield (PLQY) of 20%, highlighting the potential of colloidal chemistry methods to study the full diversity of Ruddlesden–Popper phases .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from the double perovskites, CsCdCl 3 has emerged as a novel afterglow material recently. ,,, He et al first reported a hexagonal-phase Mn 2+ -doped CsCdCl 3 perovskite with a long afterglow duration up to 1480 s . Despite the rich traps, a high PL QY up to 91.4% was realized by adjusting the doping concentration of Mn ions.…”
mentioning
confidence: 99%